Rationally optimized carrier effective mass and carrier density leads to high average ZT value in n-type PbSe. Issue 40 (5th October 2021) - Xiao, Yu; Liu, Wei; Zhang, Yang; Wang, Dongyang; Shi, Haonan; Wang, Sining; Jin, Yang; Qu, Wanbo; Wu, Haijun; Ding, Xiangdong; Sun, Jun; Zhao, Li-Dong
Abstract : In thermoelectric materials, carrier effective mass and carrier density are two key parameters to determine the electrical transport properties. Therefore, rationally optimizing these two parameters can largely enhance the power factor and ZT value. Abstract : Among the intricately coupled thermoelectric parameters, carrier effective mass ( m *) and carrier density ( n ) are two key parameters to determine the electrical transport properties. To enhance the broad-temperature thermoelectric performance in n-type PbSe, this work elaborately optimizes its power factor with the intrinsically proportional relationship between carrier effective mass and carrier density, n ∼ ( m *) 3/2 . Herein, the carrier effective mass in n-type PbSe is first optimized with Sn alloying and undergoes a decrease from ∼0.34 m e in PbSe to ∼0.25 m e in Pb0.77 Sn0.23 Se because of band sharpening. This reduced carrier effective mass contributes to an obvious enhancement of carrier mobility, thereby boosting the maximum power factor from ∼16.8 μW cm −1 K −2 in PbSe to ∼20.5 μW cm −1 K −2 in Pb0.85 Sn0.15 Se. Moreover, to match the reduced carrier effective mass in n-type Pb0.85 Sn0.15 Se, its carrier density is well tuned with Ag counter doping, which further facilitates a high average power factor in the whole working temperature range. The average power factor in Pb0.85 Sn0.15 Se systems increases from ∼15.6 μW cm −1 K −2 with a carrier density of ∼6.21 × 10 19 cm −3 to ∼17.6 μW cm −1 K −2 with a carrier density of ∼2.12 × 10 19 cm −3 at 300–873 K. Finally, an average ZT ( ZT ave ) of ∼0.95 is achieved in the n-type Pb0.85 Sn0.15 Se sample at 300–873 K, and the sample outperforms most other n-type PbSe-based thermoelectric materials.